1990
DOI: 10.1152/jappl.1990.68.1.374
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils are not necessary for induction of ischemia-reperfusion lung injury

Abstract: Ischemia-reperfusion lung injury limits lung transplantation. Neutrophil activation and/or xanthine oxidase-mediated purine degradation may cause toxic oxygen metabolite production and lung injury. We investigated whether circulating blood elements are involved in the pathogenesis of ischemia-reperfusion lung injury. Isolated rat lungs were perfused with physiological salt solution (PSS) stabilized with Ficoll until circulating blood elements were not detected in the lung effluent. Lungs were then rendered isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 0 publications
1
38
0
1
Order By: Relevance
“…Ischemia/reperfusion injury has also been described in the lung, although the metabolic mechanisms have not yet been elucidated (5)(6)(7)(8)(9)(10). It is important to note that unlike other organs, ischemia of the lung does not result necessarily in tissue hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemia/reperfusion injury has also been described in the lung, although the metabolic mechanisms have not yet been elucidated (5)(6)(7)(8)(9)(10). It is important to note that unlike other organs, ischemia of the lung does not result necessarily in tissue hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Although neutrophils play an important role in perpetuating lung IR injury, the role of neutrophils in the early phase is less predominant. Studies from Deeb and colleagues have shown that during the first few hours of IR injury, it is the neutrophil-independent events that play a major role and that neutrophil-dependent events exert their effects after several hours of reperfusion (Deeb, et al, 1990). Other studies have confirmed this biphasic cellular response and have suggested that T cells and macrophages have a more prominent role in the early phase of IR injury while neutrophils play a late, effector role in the execution of lung IR injury (Eppinger, et al, 1995;Fiser, et al, 2001).…”
Section: Neutrophilsmentioning
confidence: 99%
“…4 Although pulmonary endothelial cells, smooth muscle cells, lung macrophages and neutrophils have been implicated, [6][7][8][9]12,[31][32][33] this is still controversial. 5,11,30 Moreover, although there are many oxidase enzymes capable of forming superoxide in the lung (eg, xanthine oxidase, arachidonic acid peroxidases, nitric oxide synthase (all of which are present in endothelial cells), NADPH oxidase and NADH oxidase), 34 it remains to be determined which is predominant. 11 Bursts of oxidant formation within several minutes of reperfusion have been observed in other organs, and xanthine oxidase-derived oxidants have been proposed as the source.…”
Section: Time Course and Possible Sources Of Oxygen Free Radical Genementioning
confidence: 99%
“…2,3 The same mechanism appears to be involved in the effect of ischemia-reperfusion on the pulmonary circulation, 4 but it remains unclear how oxygen free radicals are generated after a short period of occlusion of the pulmonary artery alone. Most previous studies investigating oxygen free radicals in reperfusion injury of the lungs have been performed in isolated lungs, 1,[5][6][7][8][9] or in animals with obstruction of both the airway and the pulmonary artery; that is, hilar occlusion. [10][11][12] In order to simulate clinical pulmonary artery occlusion and reperfusion, the generation of oxygen free radicals should be evaluated without obstructing either the airway or the bronchial circulation in in-vivo blood-perfused lungs.…”
mentioning
confidence: 99%